2013
DOI: 10.4168/aair.2013.5.5.258
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Genetic Basis of Aspirin Hypersensitivity in Asthma Beyond Arachidonate Pathways

Abstract: Although aspirin-exacerbated respiratory disease (AERD) has attracted a great deal of attention because of its association with severe asthma, it remains widely under-diagnosed in the asthmatic population. Oral aspirin challenge is the best method of diagnosing AERD, but this is a time-consuming procedure with serious complications in some cases. Thus, development of non-invasive methods for easy diagnosis is necessary to prevent unexpected complications of aspirin use in susceptible patients. For the past dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 128 publications
(121 reference statements)
0
41
0
Order By: Relevance
“…Although many genetic variations have been reported to serve as potential markers of the AERD or CRSwNP phenotype, it has been suggested that that HLA DPB1 Ã 0301 reliable genetic marker of CRSwNP in AERD patients, as patients carrying this allele exhibited a significantly higher prevalence of CRSwNP than did those without the allele [31,32]. A recent study [33 & ] showed that serum periostin level is a potential biomarker of AERD, especially AERD with CRSwNP.…”
Section: Diagnosismentioning
confidence: 99%
“…Although many genetic variations have been reported to serve as potential markers of the AERD or CRSwNP phenotype, it has been suggested that that HLA DPB1 Ã 0301 reliable genetic marker of CRSwNP in AERD patients, as patients carrying this allele exhibited a significantly higher prevalence of CRSwNP than did those without the allele [31,32]. A recent study [33 & ] showed that serum periostin level is a potential biomarker of AERD, especially AERD with CRSwNP.…”
Section: Diagnosismentioning
confidence: 99%
“…954 However, much of the described pathophysiology of AERD is likely explained by genetic variations, of which a number of polymorphisms have been identified that potentially play a causative role. [955][956][957] These polymorphisms are thought to alter enzyme kinetics and receptor sensitivity. As a result the activity of LT-synthase is increased, leading to an overproduction of cysteinyl LTs (cysLTs).…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
“…There are relatively small studies in multiple ethnicities, and many of the reports may reflect specific genetic influences limited to a single population (see Tables E1-E5 in this article's Online Repository at www.jaci-inpractice.org). 17…”
Section: Geneticsmentioning
confidence: 97%